THE EFFECT OF HYBRID SAVONIUS AND DARRIEUS TURBINE ON THE CHANGE OF WAKE RECOVERY AND IMPROVEMENT OF WIND ENERGY HARVESTING IMPROVEMENT - Erwin, Erwin; Adi, Surjosatyo; Julianto, Sulistyo Nugroho; Mahlia, Teuku Meurah Indra; Soemardi, Tresna Priyana (Journal of Applied Engineering Science, 2018)
The energy crisis encourages the development of renewable energy; one of the potential renewable energy is wind. In the field of wind turbine there is a two-way development of the utilization of wind energy, first by making a large wind turbine, the second by making a wind farm energy with a relatively small wind turbine. This hybrid vertical axis wind turbine (VAWT) is designed to work optimally on a farm array, on a wind turbine farm array will always cause a wake effect that will reduce overall wind turbine and farm array performance, an investigation with a Computational Fluid Dynamics (CFD) simulation is required to predict how far the wake effect will be before farm array build. The use of simulation software has been widely used to predict the effects of this wake, and experiments in the laboratory have also been done to predict the effects of a wake as well. This study’s purpose is to predict the distance area of the recovery wake behind the wind turbine, this distance which will be the reference distance between wind turbine units and determining the density of the turbine in a farm. Simulation using CFD, with a method of Multi Frame Reference (MRF). Analysis using descriptive and inferential method in statistics such as mean, Kolmogorov-Smirnov Z, and Kruskal Walis test. From the analysis of simulation results and data processing descriptively and analytic statistic, from the data given, the distance of x/D=4, wind speed has recovery to the value near the input speed and no significant change to x/D= 9. Then it can be concluded that the distance between two wind turbines that can be used is a distance of 3.6 meters. These data suggest that the hybrid farm array VAWT savonius and darrieus have a higher power density compared to HAWT. From power density calculation the hybrid VAWT has a greater electrical potential up to 300 percent compared to the HAWT farm array.